2016
DOI: 10.3390/ijms17081359
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Releasing Peptide-2 Attenuation of Protein Kinase C-Induced Inflammation in Human Ovarian Granulosa Cells

Abstract: Cyclooxygenase-2 (COX-2) and interleukin-8 (IL-8) are two important inflammatory mediators in ovulation. Ghrelin may modulate inflammatory signaling via growth hormone secretagogue receptors. We investigated the role of ghrelin in KGN human ovarian granulosa cells using protein kinase C (PKC) activator phorbol 12, 13-didecanoate (PDD) and synthetic ghrelin analog growth hormone releasing peptide-2 (GHRP-2). GHRP-2 attenuated PDD-induced expression of protein and mRNA, the promoter activity of COX-2 and IL-8 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Therefore, KGN cells are considered a valuable model for the study of steroidogenesis, cell growth, and apoptosis regulation in human GCs [ 57 , 58 ]. Furthermore, it has been discovered that KGN cells express the GHSR gene and are responsive to stimulation by ghrelin analog growth hormone-releasing peptide-2 [ 59 ]. Therefore, this study selected KGN cells to explore the relationship between miR-128-3p and GHSR gene expression and their effects on the proliferation and apoptosis of KGN cells.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, KGN cells are considered a valuable model for the study of steroidogenesis, cell growth, and apoptosis regulation in human GCs [ 57 , 58 ]. Furthermore, it has been discovered that KGN cells express the GHSR gene and are responsive to stimulation by ghrelin analog growth hormone-releasing peptide-2 [ 59 ]. Therefore, this study selected KGN cells to explore the relationship between miR-128-3p and GHSR gene expression and their effects on the proliferation and apoptosis of KGN cells.…”
Section: Methodsmentioning
confidence: 99%
“…PMA can exert effects by the phosphorylation of mitogen-activated protein kinases (MAPKs), such as extracellular regulated protein kinase (ERK) 1/2, p38 and c-Jun N-terminal kinase (JNK) (Shankar et al 2016;Chao et al 2016;Chen et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, ghrelin may influence ovarian steroidogenesis and oocyte maturation 8,9 . More recently researches reported that ghrelin may also have direct effects ovarian granulosa cells to influence the expression of Anti‐Mullerian hormone (AMH) 10 …”
Section: Introductionmentioning
confidence: 99%
“…wileyonlinelibrary.com/journal/aji 1 of 6 https://doi.org/10.1111/aji.13579 ovarian granulosa cells to influence the expression of Anti-Mullerian hormone (AMH). 10 AMH is a peptide growth factor belongs to the transforming growth factor-β (TGF-β) family, and is produced by granulosa cells of growing follicles. 11 AMH levels are unaffected by hormonal contraceptives, more sensitive and specific than other measures of ovarian reserve.…”
Section: Introductionmentioning
confidence: 99%